Design and experiment of the pneumatic cylinder type precision metering system for wheat - Abdallah, Anas Dafaallah; Liao, Qingxi; Ibrahim, Elebaid Jabir; Wang, Lei (International Journal of Agricultural and Biological Engineering, 2023)
The main goal of this study was to design a pneumatic cylindrical-type metering device with six-rows for wheat precision and to analyze its output under different rotating speeds and vacuum pressure values. The effect of the pressure, rotating speed and rows on seed suction, retention and dropping was shown inspected. Six levels of rotating speed (5, 10, 15, 20, 25 and 30 r/min.) combined with the applying of different vacuum pressures (1.8, 2.1, 2.4, 2.7, 3.0, and 3.3 kPa) were inspected to detect the optimum pressure which was adequate for seed sucking at each speed. In addition, to predict the vacuum pressure corresponding with each rotating speed, a regression model was developed. Based on seed mass analysis, statistical differences under the influence of velocities and negative pressure were found at 5 percent significance according to Duncan's Test, whereas the differences were existed between and within rows. Results revealed that the highest seed mass means of 19.02 g and 22.64 g were obtained by row1while the lowest means of 18.02 g and 21.49 g were attained by row6 under the effect of the speed and vacuum pressure, respectively. The noticeable variation between row1 and row 6, particularly under high speeds (25 and 30 r/min), might be returned to the truth that row 1 was closer to vacuum inlet, and row 6 was the farthest one. Results concluded that the multiple-row pneumatic cylinder with oblong shape seed nozzle was found to be capable for single seed picking with a small rows variation but without seed damage. Keywords: multi-rows cylinder, pneumatic metering device, wheat, precision DOI: 10.25165/j.ijabe.20231605.7444 Citation: Abdallah A D, Liao Q X, Ibrahim E J, Wang L. Design and experiment of the pneumatic cylinder type precision metering system for wheat. Int J Agric & Biol Eng, 2023; 16(5): 88–94.